A Skill Building Social Media About Forest Tourism: Peningkatan Keahlian Pembuatan Media Sosial Tentang Wisata Hutan - Sari, Fadela Yunika; Wulandari, Christine; Budiono, Pitojo; Erdian , Zeda; Kurniawan, Vinanda Arum Tri; Apriliani, Adella Putri; Saputra, Pindo Riski; Putra, M. Aditya; Aina, Erni Vida; Triana, Heni; Jumaiyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Social media helps tourist destinations build their image and branding. By sharing interesting visual content, traveler experience stories, and positive testimonials, tourist destinations can strengthen their identity in the public eye. The use of social media also allows a tourist destination to interact directly with tourists, by answering questions, providing recommendations, and sharing personal tourist experiences. This study aims to determine the respondents' level of understanding of the creation of social media about forest tourism in increasing the visibility and attractiveness of tourism in Lampung province, focusing on theories that support the role of social media in influencing tourist decisions. Respondents in this study amounted to 28 people who were parties to the Government Office which included the Tourism Office, Hiudp Environmental Service, Forestry Service, SDA Pesawaran, KPH Pesawaran, and Tahura. The implementation of this community service activity was carried out using lecture and FGD (Focus Group Discussion) methods conducted directly by lecturers of the Forestry Department and Social Media Training Resource Persons by Lampung Geh. The results of the pre-test and post-test show that if there is an increase in participants' understanding of social media related to ecotourism. The data analysis conducted shows a significant increase in participants' knowledge, this reflects the material provided by the resource person can be understood by the participants. The percentage of the pre-test value is 66% while for the post-test value is 95%, so there is an increase of 29%.